2021
DOI: 10.17576/jsm-2021-5011-25
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Higher Education in the Presence of Shared Inputs using Data Envelopment Analysis

Abstract: This study measures the efficiency of higher education institutions with respect to teaching activity, research activity, and overall activities and also provides a direction for low-performing institutions to improve their performance. In many instances, the efficiency of the institution is a sum up of the efficiency of its activities. However, when the activities consume some resources in common, it requires the allocation of shared resources among the activities. Since sums up the efficiency of each activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…They found that both efficiency and quality in the Columbian universities has been decreased in the observed period. Gebru et al (2021) have analysed the efficiency of higher education in Pakistani HEIs from 2017 to 2018. They have implemented DEA methodology for measuring the overall efficiency of HEIs, and, thereafter eliminated "the sensitivity of efficiency scores using the bootstrap technique".…”
Section: Efficiency Of Tertiary Educationmentioning
confidence: 99%
“…They found that both efficiency and quality in the Columbian universities has been decreased in the observed period. Gebru et al (2021) have analysed the efficiency of higher education in Pakistani HEIs from 2017 to 2018. They have implemented DEA methodology for measuring the overall efficiency of HEIs, and, thereafter eliminated "the sensitivity of efficiency scores using the bootstrap technique".…”
Section: Efficiency Of Tertiary Educationmentioning
confidence: 99%
“…They found that both efficiency and quality in the Columbian universities has been decreased in the observed period. Gebru et al (2021) have analysed the efficiency of higher education in Pakistani HEIs from 2017 to 2018. They have implemented DEA methodology for measuring the overall efficiency of HEIs, and, thereafter eliminated "the sensitivity of efficiency scores using the bootstrap technique".…”
Section: Efficiency Of Tertiary Educationmentioning
confidence: 99%